Adsorption of Levofloxacine Antibacterial from Contaminated Water by Non – Conventional Low Cost Natural Waste Materials (Journal of Engineering, 2014)
An experimental study was conducted with low cost natural waste adsorbent materials, barley husks and eggshells, for the removal of Levofloxacine (LEVX) antibacterial from synthetic waste water. Batch sorption tests were conducted to study their isothermal adsorption capacity and compared with conventional activated carbon which were, activated carbon > barley husks > eggshells with removal efficiencies 74, 71 and 42 % with adsorbents doses of 5, 5 and 50 g/L of activated carbon, barley husks, and eggshells respectively. The equilibrium sorption isotherms had been analyzed by Langmuir, Freundlich, and Sips models, and their parameters were evaluated. The experimental data were correlated well with the Langmuir model which gives the best fit for LEVX adsorption / biosorption on to activated carbon, barley husks, and eggshells respectively.The adsorption capacity was almost dependent on temperature. The thermodynamic parameters associated with the adsorption process, ΔGo , ΔHº and ΔSº were reported and it is suggested to be physisorption, and of exothermic nature.